The Empowerment of Digital Literacy Aspects in Education Policy: Supporting Young Generation's Preparability for the Digital Era Literature Review - Suratno, Ujang; Nursidi, Didi; Cahyanto, Iman (Formosa Journal of Applied Sciences, 2024)
This research aims to investigate the importance of the empowering aspects of digital literacy in education policy to support young people's readiness for the digital age. Utilizing a structured approach, this research conducted a deep analysis of the relevant literature and presented data and findings that support the argument. The literature review highlights the concept of digital literacy, its impact on everyday life, and the need for integration into the education system. The research methodology involved a critical analysis of various sources related to the topic, including scientific journals, textbooks, and research reports. The findings show that the empowerment of digital literacy in education policy has a positive impact on preparing young people for the challenges and opportunities of the digital age.orts. The findings show that the empowerment of digital literacy in education policy has a positive impact on preparing young people for the challenges and opportunities of the digital age.